2019
DOI: 10.3389/fpls.2019.01589
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Non-Mycorrhizal Fungi in Germination of the Mycoheterotrophic Orchid Pogoniopsis schenckii Cogn.

Abstract: Endophytic fungi are those that inhabit within organs and tissues without causing damage, while mycorrhizal fungi develop hyphal complexes called pelotons within cortical cells of orchid roots. Although abundant and frequent in all plant organs, the role of endophytic fungi has been neglected in relation to orchid’s early development. Pogoniopsis schenckii Cogn. is an aclorophyllated and mycoheterotrophic (MH) orchid. This study aimed at i) investigating the endophytic fungal community in organs of P. schencki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 57 publications
0
27
0
1
Order By: Relevance
“…A total of 14,800 OTUs belonging to 4 phyla, 73 families, and 99 genera obtained from tissues and rhizosphere soils were analyzed. It was previously reported that mycorrhizal fungi associated with orchids were mainly Basidiomycota and Ascomycota (Sisti et al 2019). In our study, Ascomycota (33.71%-86.38%)…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A total of 14,800 OTUs belonging to 4 phyla, 73 families, and 99 genera obtained from tissues and rhizosphere soils were analyzed. It was previously reported that mycorrhizal fungi associated with orchids were mainly Basidiomycota and Ascomycota (Sisti et al 2019). In our study, Ascomycota (33.71%-86.38%)…”
Section: Discussionmentioning
confidence: 92%
“…Endophytes can not only promote plant growth but also produce bioactive components (Sisti et al 2019 Ng et al (2013) declared that the genome of UM238, a dematiaceous fungus belonging to Herpotrichiellaceae, contained a variety of protective genes that helped the fungus survive in adverse environments. We also found that the abundance of Herpotrichiellaceae in roots was high, with the highest at the LD collection site; this family may aid G. conopsea adaptation to the environment of the Qinghai-Tibet Plateau, which is characterized by low temperature, strong UV ultraviolet light and low oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…In nature, this is achieved by mycorrhizal symbiosis, which is discussed later in this review. Germination usually takes several months to a year [ 20 ] since germinating orchid seeds do not directly produce leaf and root primordia. Instead, a protocorm develops during the germination process.…”
Section: Through the Looking Glass: How Orchids Naturally Establismentioning
confidence: 99%
“…Most recognized OMF genera are basidiomycetous fungi with an anamorphic stage resembling the well-known plant pathogen, Rhizoctonia , and are named “ Rhizoctonia -like fungi” [ 26 , 29 ]. Though uncommon, studies showing non- Rhizoctonia -like fungi forming OM have increased since the early 2000s [ 20 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Those genera include strong pathogen [ 6 , 30 , 33 , 38 ], saprobes [ 39 , 40 ], ectomycorrhizal fungi [ 41 , 42 ], and ascomycetous fungi [ 20 , 43 ].…”
Section: Through the Looking Glass: How Orchids Naturally Establismentioning
confidence: 99%
See 1 more Smart Citation